ENHANCING DEMOCRATIC QUALITY IN INDONESIA’S REGIONAL ELECTIONS: GOVERNANCE DYNAMICS AND TECHNOLOGICAL PATHWAYS - Ferdian Ahya Al Putra; Badriyatus Salma; Febrianti Nur Qothimah (Politik Indonesia: Indonesian Political Science Review, 2025)
The discourse on regional head elections through the Regional People's Representative Council (DPRD) has sparked both pros and cons among the public. The large budget and money politics are the reasons for this discourse. This has led some to question the rationality of the plan, as it is considered capable of minimizing public involvement and weakening democracy. However, various strategies exist to create more efficient regional elections. This study aims to discuss efforts to enhance the quality of democracy by creating more efficient regional head elections. The novelty of this research lies in the re-emergence of the discourse on indirect regional elections. Accordingly, this study seeks to identify which aspects of election budgeting contribute to inefficiency and to propose possible strategies to address these issues. This includes discussing the potential of combining judicial review mechanisms amid the risks associated with the adoption of technology in elections. The findings show that the main problems in regional elections—such as high political costs, money politics, oligarchic dominance, and weak transparency—are structural and institutional rather than caused solely by the direct election system. Therefore, improving local democracy should focus on reforming candidate recruitment, strengthening political funding accountability, and enhancing public oversight and political education. In addition, the integration of election technology has the potential to improve efficiency and transparency if supported by institutional readiness and efforts to reduce the digital divide.